2008
DOI: 10.1002/jssc.200800095
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins in capillary electrophoresis enantioseparations – Recent developments and applications

Abstract: Capillary EKC has been established as a versatile and robust CE method for the separation of enantiomers. Within the chiral selectors added to the BGE CDs continue as the most widely used selectors due to their structural variety and commercial availability. This is reflected in the large number of practical applications of CDs to analytical enantioseparations that have been reported between January 2006 and January 2008, the period of time covered by this review. Most of these applications cover aspects of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 192 publications
0
102
0
3
Order By: Relevance
“…Since the chemical synthesis of enantiomers usually gives rise to racemic compounds, chiral separation is of utmost importance. Current approaches are based on direct gas chromatography [7] or HPLC (High Pressure Liquid Chromatography) [37], capillary electrophoresis [34], or NMR (Nuclear Magnetic Resonance) anisotropy methods [38]. They suffer from the drawbacks that they are slow and only yield endpoint results, i.e., they do not provide any information about the dynamics of the separation process.…”
Section: Left-and Right-handed Enantiomermentioning
confidence: 99%
“…Since the chemical synthesis of enantiomers usually gives rise to racemic compounds, chiral separation is of utmost importance. Current approaches are based on direct gas chromatography [7] or HPLC (High Pressure Liquid Chromatography) [37], capillary electrophoresis [34], or NMR (Nuclear Magnetic Resonance) anisotropy methods [38]. They suffer from the drawbacks that they are slow and only yield endpoint results, i.e., they do not provide any information about the dynamics of the separation process.…”
Section: Left-and Right-handed Enantiomermentioning
confidence: 99%
“…From these reports it can be concluded that almost the entire primary rim and some of the secondary rim is sulfonated and negatively charged. Sulfonated ␤-CDs are used in chromatography and especially in capillary electrophoresis for the enantiomeric separation of compounds [12]. However, there have been very few studies carried out on the inclusion of guest molecules within the cavity of the sulfonated ␤-CDs.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical synthesis of chiral molecules usually produces a racemic mixture, with equal amounts of both enantiomers, and their separation based on chirality is of importance in fields ranging from agriculture to food and pharmaceutical industries. Currently favored approaches rely on gas, liquid or capillary electromigration chromatography [2], requiring costly chiral media. Thus, simpler, alternative approaches to chiral separation are desirable.…”
mentioning
confidence: 99%